EFFECTS OF SHORT-TERM CROP ROTATION SYSTEMS ON THE GROWTH AND DEVELOPMENT OF COTTON - Ismailov Dauletbay Uzaqbaevich (European Journal of Agricultural and Rural Education, 2022)
In the Republic of Karakalpakstan, field experiments were conducted to determine the impact of short-term crop rotation systems on the growth and development of the soil. According to the results of the experiments, the methods of sowing short-term crop rotation and the introduction of winter wheat, repeated and interval crops, the positive effects of applied organic fertilizers were determined. In this case, the crop rotation is 1:2, grain: cotton: in the cotton system, after the winter wheat, repeated crop (corn) + interval (mung bean) + 20 t / ha of manure, which is positive for the growth and development of cotton during the next two years.